District/City Fiscal Dependence Analysis in Regional Development in Lampung - Agustinus Eko Kurniawan; Teguh Endaryanto; Dwi Haryono (EKO-REGIONAL, 2023)
The contribution of original local government revenue to total regional revenue in regencies and cities in Lampung Province is relatively low, under 20%, especially in the new autonomous regions that were formed in 1999. This study aims to analyze regional fiscal dependence, analyze regional fiscal dependence related to the dominant business sector, and analyze the ratio of regional taxes and retribution to GRDP. This study uses a quantitative descriptive method. Data collection in the period 2016-2021. The analytical method used is descriptive quantitative analysis, through the calculation of the Fiscal Autonomy Index, which was developed by Hunter, 1977 and adapted to the structure of the regional revenue and expenditure budget. The results of the study indicate that the value of the fiscal dependence of the regions studied is in a high dependency status or not yet independent, except for Metro City which in 2021 managed to increase its status to become self-reliant. Furthermore, all regions with dominant primary business sectors, namely the agriculture, forestry, and fisheries sectors and the mining and quarrying sectors have a high dependency status or are not yet independent. The ratio of regional taxes and retribution to GRDP, in all regions studied is still very low. Efforts that need to be made by local governments to increase regional fiscal independence include calculating the real potential of regional taxes and retribution, developing potential sectors in increasing regional tax and retribution sector revenues, utilizing information technology, adjusting regional taxes and retribution, accelerating regional investment, developing local economy, and increased infrastructure capital spending. The difference between this research compared to previous research is that this research provides policy recommendations to local governments to increase local revenue and reduce dependence on funds.Keywords: Fiscal Dependence, Regional Development, Ratio of Regional Taxes and Retribution to GRDP